2022
DOI: 10.2196/40101
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Integrated Intervention to Reduce the Impact of HIV Stigma on HIV Treatment Outcomes Among Adolescents Living With HIV in Uganda: Protocol for a Randomized Controlled Trial

Abstract: Background HIV stigma remains a formidable barrier to HIV treatment adherence among school-attending adolescents living with HIV, owing to high levels of HIV stigma within schools, rigid school structures and routines, lack of adherence support, and food insecurity. Thus, this protocol paper presents an evidence-informed multilevel intervention that will simultaneously address family- and school-related barriers to HIV treatment adherence and care engagement among adolescents living with HIV attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 161 publications
1
2
0
Order By: Relevance
“…14 There is growing evidence that ALHIV (15-24 years) had 59% higher attrition than adults (25-54 years) one year after initiating ART underscoring the need to develop and test interventions to improve retention that specifically target adolescents. 33 Consistent with a recent systematic review of 154 adult HIV patient cohorts in low-and middle-income countries, on average, 83% of patients were retained in HIV treatment services after 12 months on ART, but only 60% were retained after 60 months on ART. 34 As countries begin to implement the WHO-recommended "Test and Treat" strategy, all individuals who test HIV positive will immediately initiate ART, substantially increasing the number of ART.…”
supporting
confidence: 71%
“…14 There is growing evidence that ALHIV (15-24 years) had 59% higher attrition than adults (25-54 years) one year after initiating ART underscoring the need to develop and test interventions to improve retention that specifically target adolescents. 33 Consistent with a recent systematic review of 154 adult HIV patient cohorts in low-and middle-income countries, on average, 83% of patients were retained in HIV treatment services after 12 months on ART, but only 60% were retained after 60 months on ART. 34 As countries begin to implement the WHO-recommended "Test and Treat" strategy, all individuals who test HIV positive will immediately initiate ART, substantially increasing the number of ART.…”
supporting
confidence: 71%
“…The studies included in this review are predominantly from LMICs where the extended family structure is prevalent, which is believed to be more supportive to orphaned children [ 13 , 31 , 32 ]. However, it is important to note that cultural changes and specific circumstances, such as insurgency in Kenya, can impact the prevalence of ART adherence reported in a study [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent review of interventions published between 2015 and 2019 identified 7 studies conducted in Eastern or Southern Africa [12]. While this is an encouraging increase, and additional trials are underway [13][14][15], there remains an urgent need for innovative interventions to improve ART adherence within this important population.…”
Section: Introductionmentioning
confidence: 99%